Power electronic assemblies: Thermo-mechanical degradations of gold-tin solder for attaching devices. (September 2016) - Arabi, F.; Theolier, L.; Martineau, D.; Deletage, J.-Y.; Medina, M.; Woirgard, E.
Abstract: The eutectic Au80 Sn20 solder alloy has been applied in semiconductor assemblies and other industries for years. Due to some superior physical properties, Au/Sn alloy gradually becomes one of the best materials for soldering in electronic devices and components packaging but the voids growth in AuSn solder joints is one of the many critical factors governing the solder joint reliability. Voids may degrade the mechanical robustness of the die attach and consequently affect the reliability and thermal conducting performance of the assembly. Severe thermal cycles [− 55 °C/+175 °C] have highlighted degradations in AuSn die attach solder. The inspection of as-prepared die-attachments by X-ray and SEM (observation of cross-section) shows that the initial voids sizes were increased and a propagation of transverse cracks inside the joint between voids has appeared after ageing, it was featured also the existence of the IMC typical scallop-shape morphology with the phase structure of (Ni, Au)3 Sn2 on as-reflowed joints. In this paper, we evaluate the origin of these degradations and ways to address them. Highlights: Influence of voids on the reliability of AuSn die attach material. Effects of thermal cycling on the initiation and propagation of solder cracks. Explanation of Intermetallic compounds IMC growth during ageing. FEM simulation of the occurrence of cracks upon cooling and heating. FEM Simulation of the voids growth during rapid thermal cycling (RTC).